Contrasting views on co-management of indigenous natural and cultural heritage – Case of Laponia World Heritage site, Sweden. (2020) - Stjernström, Olof; Pashkevich, Albina; Avango, Dag
Abstract: This article discusses the evaluation of the management of the Laponia World Heritage site (Laponia WHS) in northern Sweden. After inscription on the World Heritage list in 1996, difficulties emerged in establishing a common understanding about the involvement of various stakeholders into the site's management model, the key point of contention being the influence of the representatives from indigenous Sami people and how that should be organised. In 2011, the management organisation led by Laponiatjuottjudus (the Sami name for the Laponia WHS management organisation) was established and implemented. This organisation gave Sami representatives a majority in the Laponia steering board and the position as chairperson in the board. This marked a remarkable shift in the Swedish national management system of land in not only handing over a state decision-making power to the local level but also to representatives of the indigenous population. The evaluation of the management model presented by Laponiatjuottjudus resulted in a number of responses from several stakeholders participating in a consultation process. These responses, from stakeholders with conflicting positions in relation to the issue described above, are the subject of this study. The analysis of these data collected reveals the existence of four major approaches or narratives to the Laponia WHS, with narratives connected to nature, the indigenous population and local governance, the economic effects of the existing system, and lastly the local community narrative. The study concludes that present management of Laponia WHS, the Laponiatjuottjudus, is a unique attempt to widen the management and planning process that partly interferes with the existing national planning model. At the same time, the analysis reveals that the Sami demands for influence over land management in the north still faces major challenges connected to its colonial legacy.